Macrophage Zc3h12c limits tissue inflammation and injury via alternative splicing of pre-mRNA - Li, Chenyu; Marschner, Julian Aurelio; Kusunoki, Yoshihiro; Zhang, Ningxin; Li, Xiaoxin; Deng, Hao; Zhao, Zhibo; Watanabe-Kusunoki, Kanako; Zhu, Zhihui; Xu, Yan; Steiger, Stefanie; Lech, Maciej; et al. (Advanced science, 2025)
RNA-binding proteins regulate post-transcriptional gene translation, but the macrophage-specific role of Zc3h12c remains poorly characterized. Here, the role of Zc3h12c in macrophages is characterized using Tnfrsf11aCre-Zc3h12cflox/flox mice. Both Tnfrsf11a and Zc3h12c are highly expressed in the kidney tissue from patients with chronic kidney disease and showed a positive association with an interstitial fibrosis score. Single cell RNA sequencing demonstrated abundant Tnfrsf11a expression in murine kidney macrophages and a correlation with the induction of chemokines, macrophage phagocytosis, and activation upon kidney injury. In various kidney injury models, Tnfrsf11aCre-Zc3h12cflox/flox mice suffered from more injury and inflammation in the kidney, characterized by an increase in Ccr2 positive leukocyte infiltration. Mechanistic in vitro studies revealed that Zc3h12c suppresses macrophage activation toward a pro-inflammatory phenotype, modulates macrophage survival, migration, and phagocytosis. Both in silico and in vitro analysis indicated that Zc3h12c regulates the pro-inflammatory cytokines/chemokines and chemokine receptors expression and modulates the alternative splicing of pre-mRNAs STAT1. Thus, macrophage-derived Zc3h12c limits tissue inflammation and injury, potentially via alternate splicing of pre-mRNAs.